Akulah Pokok Anggur: Eksegesis, Teologi, dan Implikasi Pastoral Perikop Yohanes 15:1–8 dalam Konteks Spiritualitas Umat di Kalimantan Barat - Kristina Meni; Laurentius Prasetyo; Yanto Sandy Tjang (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
The study examines John 15:1–8, highlighting its Christological, ecclesiological dimensions, and pastoral implications in a contemporary context, particularly in West Kalimantan. Employing an exegetical approach integrated with theological reflection, the metaphor of the “true vine” is understood as a declaration of Jesus’ identity as the source of authentic life and the relational foundation of the community of disciples. The concept of “abiding” is interpreted as an ongoing existential connectedness with Christ, expressed through practices of faith such as engagement with the Word, prayer, and love. Meanwhile, “bearing fruit” is not merely ethical output but an authentic manifestation of life grounded in this relational union. Furthermore, the study argues that Johannine ecclesiology is organic in nature, portraying the church as a living community deriving its existence from and in Christ, rather than a purely institutional structure. The pastoral implications of this metaphor are significant in addressing local challenges such as individualism, ecological crisis, religious plurality, and the spiritual formation of youth. Using a praxis–reflection–praxis framework, the text is integrated into theological education as a model linking faith reflection with concrete action. The findings affirm that Christ-centered spirituality fosters personal and communal transformation relevant to the contemporary church.